China's Capital Flight: Pre- and Post-Crisis Experiences - Yin-Wong Cheung; Sven Steinkamp; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study China's illicit capital flow and document a change in its pattern. Specifically, we observe that China's capital flight, especially the one measured by trade misinvoicing, exhibits a weakened response in the post-2007 period to the covered interest disparity, which is a theoretical determinant of capital flight. Further analyses indicate that the post-2007 behavior is influenced by quantitative easing and other factors including exchange rate variability, capital control policy and trade frictions. Our study confirms that China's capital flight pattern and its determinants are affected by the crisis event. Further, both the canonical and additional explanatory variables have different effects on different measures of capital flight. These results highlight the challenges of managing China's capital flight, which requires information on the period and the type of capital flight that the policy authorities would like to target.
Keywords: F30; F32; G15; 330; world bank residual method; trade misinvoicing; quantitative easing; capital controls; covered interest disparity